PERAN PROPHETIC EDUCATION DALAM MEMBANGUN KARAKTER KEPEMIMPINAN PADA ANAK USIA DINI - Nur Ilahiah; Mubair Agustin; Badru Zaman (Raudhah - Proud To Be Professional, 2023)
The success of the prophet in educating children resulted in a concept which is often referred to as prophetic education. Prophetic education is very important to be implemented in educational institutions, including in early childhood education. The prophet referred to in this research is the Prophet Muhammad Sollallohu alaihi wasallam. Prophet Muhammad Shollallohu Alaihi Wasallam is the best example (role model) in the Islamic religion. In essence, education not only teaches cognitive abilities, but also builds strong human character. One of the characters that must be optimized in children is leadership character. The aim of this research is to reveal the role of prophetic education in building leadership character in early childhood. In this research, the method used is a descriptive qualitative research method with a case study type of research. Data collection techniques through interviews and observations. The research results show that giving a mandate is one step to foster a leadership spirit in early childhood. This is in line with the concept of prophetic education where there are four contextualizations of the Prophet's characteristics that can be applied in early childhood education, namely Shidiq, Amanah, Tabligh, and Fathonah. So it can be concluded that prophetic education has an important role in building leadership character in early childhood.